2019
DOI: 10.1186/s12913-019-4130-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of WHO’s Focused Antenatal Care policy on early access, underutilisation and quality of antenatal care services in Malawi: a retrospective study

Abstract: Background A variety of antenatal care models have been implemented in low and middle-income countries over the past decades, as proposed by the World Health Organisation (WHO). One such model is the 2001 Focused Antenatal Care (FANC) programme. FANC recommended a minimum of four visits for women with uncomplicated pregnancies and emphasised quality of care to improve both maternal and neonatal outcomes. Malawi adopted FANC in 2003, however, up to now no study has been done to analyse the model’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 31 publications
(51 reference statements)
0
59
0
Order By: Relevance
“…These circumstances may have yielded limited nutrition awareness and thus unlikely for the women to remember or retain the information [ 36 ]. Other studies from sub-Saharan Africa also postulate that the poor quality of ANC is a result of low skills among health workers responsible for the nutrition education [ 11 , 37 ]. Apparently, health workers often do not utilise the standard guidelines, leading to variations in content and approaches [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These circumstances may have yielded limited nutrition awareness and thus unlikely for the women to remember or retain the information [ 36 ]. Other studies from sub-Saharan Africa also postulate that the poor quality of ANC is a result of low skills among health workers responsible for the nutrition education [ 11 , 37 ]. Apparently, health workers often do not utilise the standard guidelines, leading to variations in content and approaches [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors influence the uptake of optimal ANC contacts. Empirical studies have shown that maternal age [4], educational level [8], planned pregnancies [9], and timing of first ANC visit [10] are factors associated with adequate ANC visits. In addition, exposure to mass media, family income, and accessibility of the obstetric service are also associated with increased utilization of antenatal care [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A range of government, non-profit and private providers are involved in family planning and other reproductive health services; however, only government institutions provide the services without any charge. 4 However, existing resources are not enough for the reproductive healthcare needs of the population; only 65% of these facilities provide prenatal services and there are only 0.2 doctors and 3.4 nurses and midwives 10,000 people in the country. 4 The effect of inadequate healthcare infrastructure gets aggregated by low health literacy, lack of awareness, cultural beliefs and perceived need for pregnancy care.…”
Section: Introductionmentioning
confidence: 99%
“… 4 However, existing resources are not enough for the reproductive healthcare needs of the population; only 65% of these facilities provide prenatal services and there are only 0.2 doctors and 3.4 nurses and midwives 10,000 people in the country. 4 The effect of inadequate healthcare infrastructure gets aggregated by low health literacy, lack of awareness, cultural beliefs and perceived need for pregnancy care. 5 Even when service is available, one’s perception of pregnancy and healthcare needs can act as a barrier to availing the existing services.…”
Section: Introductionmentioning
confidence: 99%